(untitled) (Research, Society and Development, 2025)
Objective: The objective of this article was to identify factors that converge in relation to the profile of patients affected by alcohol dependence and, thus, facilitate the search for actions that aim to reduce this disease. Methodology: The information for this study was obtained through the analytical-observational method, through the analysis of medical records in a private psychiatric clinic in the city of Cascavel, in the state of Paraná (PR), Brazil, and data found on age, sex, length of stay in a psychiatric institution and diseases associated with the main diagnosis: mental and behavioral disorder due to alcohol use - dependence syndrome were tabulated. Conclusion: The majority presence of males was significant, unlike age, which did not demonstrate significant prevalence. Regarding the associated diseases, the most commonly found were mental and behavioral disorders due to cocaine use and bipolar affective disorder. Regarding the length of stay in the clinic, the study demonstrated that the majority followed the 3-month hospitalization standard (allowed by Brazilian legislation in cases of involuntary hospitalization) and were discharged close to this period. Furthermore, it was possible to observe that such data converge with studies present in the literature, demonstrating that the epidemiological profile found has similarities between other regions of the world.